Pengaruh Brand Equity, Online Customer Review Dan Content Marketing Terhadap Minat Pembelian Brownies Amanda Di Kota Malang - Rohadi, Sabrina Malika Putri; Wahono, Budi; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to examine the influence of brand equity, online customer reviews, and content marketing on the interest in buying Amanda Brownies in Malang City. Amanda Brownies is one of the brownie brands that is growing rapidly through digital marketing strategies, especially through social media. The research approach used is a quantitative method with questionnaire dissemination techniques. The sample of this study amounted to 100 respondents obtained using the Purposive Sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression to find out the relationship between independent variables and bound variables. The results of the analysis show that simultaneously, brand equity, online customer reviews, and content marketing have a significant influence on purchase interest. However, partially, only content marketing has been shown to have a significant impact on purchase interest, while brand equity and online customer reviews do not show a significant impact. These results indicate that content-based marketing strategies play a major role in encouraging consumers to buy Amanda Brownies products. Therefore, companies are advised to optimize content  marketing  strategies to increase product attractiveness and consumer buying interest. Keywords: Brand Equity, Online Customer Reviews, Content Marketing, Buying Interest, Amanda Brownies